Mapping spatial memory in teleosts: a new Frontier in neural logging techniques - Takahashi, Susumu; Sawatani, Fumiya; Ide, Kaoru; Abe, Takaaki K.; Kitagawa, Takashi; Makiguchi, Yuya (Frontiers in Physiology, 2024)
Recent advancements in microelectromechanical system technology have significantly enhanced our ability to monitor neuronal activity in free-swimming fish without disrupting their natural movement, thereby greatly improving the capabilities of neural logging using “neurologger” technology. In this review, we compiled the findings from studies applying neurologgers to teleost fish, emphasizing the discovery of various spatial-cognition cells in regions of the telencephalon analogous to the mammalian hippocampus that are deeply involved in spatial navigation. We detailed how different fish species, such as goldfish and salmonids, correlate their neural activity with environmental boundaries, head direction, speed, and other navigational cues for spatial memory and navigation strategies. We critically analyzed the similarities and differences in these mechanisms to provide insights into the evolutionary aspects of spatial cognition. We also identified gaps in current methodologies and suggest directions for future research, emphasizing the need for further exploration of spatial encoding in aquatic environments. The insights gained herein suggest the existence of a complex and evolutionarily conserved substrate for navigation and memory in vertebrates, highlighting the potential of neurologgers to expand our understanding of spatial cognition.